The Distribution of Wild Yakushima Macaque (Macaca fuscata yakui) Troops around the Coast of Yakushima Island, Japan - AZUMA, Shigeru; YOSHIHIRO, Shinichi; MARUHASHI, Tamaki; MANDA, Masaharu; KINOSHITA, Mayumi; TSUKAHARA, Takahiro; KIDO, Etsuko; MATSUSHIMA, Kana; SPRAGUE, David; KUBO, Ritsuko; AGETSUMA, Naoki; NAKAJIMA, Kensuke; et al. (Primate Research, 1998)
A series of censuses of wild Yakushima macaques (Macaca fuscata yakui) was carried out in a 127.26km2 area around the coast of Yakushima Island, Japan. The census area was estimated to have 131 troops in total. Monkeys seem to depend on natural broad-leaf forests. Troop density was highest in the western coastal area, where the greatest population of natural vegetation remained undisturbed. In total, 1, 852 monkeys were counted, giving an estimate of 2, 000-3, 850 monkeys inhabiting the census area.